23 Posters Culture Of Seduction Catalogue - Mouzouropoulos, Theseas (My University, 2015)
This inclusive conference and exhibition aimed to investigate the broad subject field of semiotics in its widest context, celebrating the exploration of connections, tensions, contradictions and complementarity between the diversity of outputs.
Keywords: Graphic Design; typography